Recovery, recovery, recovery: Monitoring recovery in professional soccer and the application of blood monitoring - Daniels, D. (2021)
The Why (Recovery in Soccer) The physical demands of match play in the English Premier League (EPL) have increased substantially in recent years [1, 2]. Interestingly the increases in high intensity workload reported do not appear to be attributed to improvements in players` physical capacity [2]. Therefore, if the physical fitness of EPL players has remained stable across time then these findings suggest players are working at a higher proportion of their physical capacity during elite matchplay [3], which highlights the increasing importance of player recovery. During a regular season, EPL players occasionally compete three times per week, particularly during the winter period. Given the volume of games required to complete a season in most top leagues, and the fixtures associated with cup competitions, it has become normal for players to be exposed to these periods of fixture congestion [4]. However, when we consider the impact of the COVID-19 era, the condensed season means playing three times a week is the new normal, and although elite players are well adapted to their sport, it is very clear that the consistent exposure to competition and limited periods of rest, places players at high risk of under recovery and its negative effects - fatigue, under-performance, higher risk of injury. The monitoring of player recovery status is therefore an important objective of sports medicine and sports science staff.